Factor analysis of the somatosensory for foot according to the instability level of snatch lifting - Moon, Y. J. (Korean Journal of Sport Biomechanics, 2020)
Objective: It is to find factors related to stability through analysis of plantar pressure factors according to the level of instability when performing Snatch. Method: Foot pressure analysis was performed while 10 weightlifters performed 80% of the highest level of Snatch, and motion was classified and analyzed in 3 grades according to the level of instability. Results: First, in Bad Motion, the movement distance of the pressure center in the direction of ML and AP was larger significantly in Phase 2. Second, in Phase 2, the number of zero-crossing in the AP direction was larger statistically significantly in Good Motion. Third, in the bad motion in Phase 3, the number of zero-crossing in the ML direction showed a significantly larger value. Fourth, in Phase 4, it was found that the more stable the lock out motion, the greater the activity of foot controlling in the left and right directions. Fifth, Phase 3, the greater the Maximum/Mean foot pressure value, the more stable the pulling action. Sixth, in Phase 2, the foot pressure was concentrated with a wide distribution in the midfoot and rearfoot. Seventh, the triggering number of the forefoot region was small in the last pull phase. Eighth, the number of triggers in the toe area was significantly higher during Good Motion in Phase 4. Conclusion: Summarizing the factors of instability in Snatch, there was no significant difference in Phase 1 for each condition. In order to enhance the stability in Phase 2, the sensory control ability in the AP direction is required, and focusing the foot pressing motion with a wide distribution in the middle and rear parts increases the instability. In Phase 3, it was found that the more unstable, the more sensory control activity was performed in the ML direction, the stronger the forefoot pressing action should be performed for a stable Snatch. In Phase 4, It is important that the feet sensory control activity in ML directions and the control ability of the toes in order to have stable Lock out motion.